The Utility of Three-Dimensional Echocardiography in the Assessment of Pulmonary Valve Function in a Novel “Hand-Made” Pulmonary Valve Conduit - Mani Ram Krishna; Vijayakumar Raju (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging, 2022)
The right ventricle to pulmonary artery valved conduit is a key component of surgeries to rehabilitate the right ventricular outflow tract in children with congenital heart disease. Evaluation of the conduit valve function forms a key part of follow-up evaluation of these children. We report the utility of three-dimensional transthoracic echocardiography to evaluate the conduit valve function in these children.